Surface-bound FXIII enhances deposition and straightness of fibrin fibers - Myra Awan; Maya Papez; Ankita P. Walvekar; Sang-Joon J. Lee; Kinjal Dasbiswas; Anand K. Ramasubramanian (Biophysical Reports)
Cross-linked fibrous networks are central to maintaining the structural integrity and functional relevance of many biological and engineered materials. Fibrin networks are the building blocks of blood clots, mediators of tissue injury and repair, and synthetic wound sealants. Cross-linking of fibrin fibers is catalyzed by the activated form of transglutaminase enzyme FXIIIa, which becomes available in plasma but is also readily presented on the surface of activated platelets and macrophages. The contribution of surface-bound FXIIIa to fibrin structure has not been well understood. In this work, we investigated the role of surface-bound FXIIIa on the formation and structure of fibrin fibers from FXIII-deficient plasma by confining the cross-linking reactions to the surface of microspheres. Quantitative microscopy revealed that cross-linking on FXIIIa-coated surfaces facilitates fibrin deposition following a sigmoidal kinetics, and that these fibers were straighter, longer, and more numerous compared with uncross-linked fibers bound to surfaces coated with anti-fibrin antibody. Our results suggest that, by modifying local fibrin density and structure, surface-bound FXIIIa may play a significant role in the mechanobiology of hemostasis and inflammation.